Digital Transformation and ESG Strategy in Global Markets: A Systematic Literature Review of Competitive and Environmental Outcomes - Ananda Rauf Nurhidayah Isnaini Isnaini (Journal of Strategic Innovation and Business Management, 2026)
Digital transformation and Environmental, Social, and Governance (ESG) strategies have become central to competitiveness in global markets, yet their strategic integration remains fragmented. This study conducts a structured systematic literature review of 25 peer-reviewed articles published between 2021 and 2026 to examine how digital transformation influences ESG performance and competitive outcomes. Guided by PRISMA 2020 procedures, the review synthesizes theoretical perspectives, sectoral patterns, methodological approaches, and core empirical mechanisms within the digital and ESG nexus. The findings show that digital transformation strengthens ESG performance primarily through green innovation, operational efficiency, governance transparency, and supply chain integration. However, these effects depend on institutional intensity, regulatory support, sectoral characteristics, and digital maturity thresholds. Evidence indicates that ESG gains are amplified in digitally advanced and regulation-intensive contexts, with mediation and moderation mechanisms shaping sustainability outcomes. The study integrates Resource-Based View, Dynamic Capabilities, Technology Organization Environment, and institutional perspectives into a Digital ESG Synergy Framework, positioning ESG performance as a structurally embedded outcome of digital capability orchestration. This synthesis advances theoretical consolidation and offers strategic insight for firms competing in digitally enabled global markets.